Increasing Students' Entrepreneurial Intentions Through Experiential Learning-Based Entrepreneurship Textbook Development - Efa Wahyu Prastyaningtyas; Widi Wulansari; Elis Irmayanti; Rino Sardanto (Dinamika Pendidikan, 2024)
Implementing entrepreneurship learning requires direct experience, not only theoretical, but must also be integrated with learning in the field. Many methods are used in learning, one of which is the experiential learning method. This research produces a product in the form of an entrepreneurship textbook based on experiential learning. The aim of this research is to develop an entrepreneurship textbook based on experiential learning to increase students' entrepreneurial intentions. The type of research used is RnD (Research and Development) with the ADDIE model. The subjects of this research were Economic Education students at Nusantara University PGRI Kediri. Data analysis uses designs including One group pretest posttest design. The results of this research indicate that textbooks are suitable for use so that they can be used by students in learning entrepreneurship, and the use of books among students provides positive and significant results in increasing entrepreneurial intentions.